Utilization of Coffee Pulp Waste Composted with Cellulolytic Actinomycetes to Enhance Chili Plant Growth - Umi Fatmawati; Dewi Puspita Sari; Meti Indrowati; Slamet Santosa; Sri Martina Wiraswati; Harlita Harlita (Journal of Tropical Biodiversity and Biotechnology, 2022)
The abundant volume of coffee bean pulp as a  by-product of the post-harvest processing is an important source of soil organic matter if it is properly handled. The alternative way to use coffee bean pulp waste to reduce the impact of environmental pollution is composting. This study aims to determine the ability of actinomycetes to degrade coffee pulp, to identify the physical and chemical characteristics of coffee pulp compost, and to evaluate the effect of coffee pulp compost on chili plant growth. The results showed that 7 isolates of actinomycetes were able to hydrolyze coffee pulp in vitro with a hydrolytic index of 1.7-3.81. The treatment of coffee pulp compost with the addition of a starter of cellulolytic actinomycetes (P2) at the end of the three-week incubation period showed the highest organic N (25 mg/kg), P (7.05 mg/kg), and K (33 mg/kg), t compared to other treatments. The effect of giving coffee pulp compost towards the growth of chili plants shows that  the coffee pulp composted with zeolite 5% (w/w) increased the height of the chili plants by 37.6%, while in coffee pulp composted by cellulolytic actinomycetes 5% (v/w) increased the number of leaves by 96% and plant biomass by 25%.  Based on the results of this research, coffee pulp compost has the potential to be used as biological fertilizer to increase plant growth, both composted by zeolite and cellulolytic actinomycetes